1969
DOI: 10.1002/macp.1969.021300111
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of oxetanes polymerization catalyzed by AlR3. Part II. Non‐stationary polymerization and chain transfer to polymer

Abstract: Polymerization of 3.3-bis(chloromethyl)oxetane induced by (iso-CqHg)3Al/H~O catalytic system proceeds in chlorobenzene solution a t 55-95 O C in homogeneous conditions. Dilatometric study in high vacuum system permitted to establish %he following main features of the process under study : irrespectively of the [(iso-C4Hg)3Al]/[HzO] ratio or [catalyst]/[monomer] ratio a gradual acceleration at the start of reaction was observed, followed by a "linear" portion, which in turn is followed by a deceleration. The wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In the late 1980s, it was shown that the amount of cyclic oligomers is drastically reduced in the presence of compounds containing hydroxyl groups . In this case, the so called “activated monomer” (AM) mechanism is more likely than the conventional “active chain end” (ACE) mechanism. In case of the AM mechanism, the active centers are located on the monomer and the polymer chain is neutral thereby strongly reducing the back‐biting process (Figure ).…”
Section: Poly(epoxide)smentioning
confidence: 99%
“…In the late 1980s, it was shown that the amount of cyclic oligomers is drastically reduced in the presence of compounds containing hydroxyl groups . In this case, the so called “activated monomer” (AM) mechanism is more likely than the conventional “active chain end” (ACE) mechanism. In case of the AM mechanism, the active centers are located on the monomer and the polymer chain is neutral thereby strongly reducing the back‐biting process (Figure ).…”
Section: Poly(epoxide)smentioning
confidence: 99%
“…The first needed reaction is formation of already mentioned dormant species: tertiary oxonium cations containing three copolymer chain branches (rate constant k AP , Scheme ). Such species were already suggested by Penczek and Kubisa4 to hamper homopolymerization of OXT, and these dormant species can be reactivated in reaction with monomer (slow reaction, the second of the reactions added to the reaction scheme, rate constant k PA , Scheme ). In many real OXT polymerization systems, but not in the analyzed one, the dormant species can also be reactivated with hydroxyl containing compounds (the resulted secondary oxonium cation–with the proton located on the ether oxygen atom–can start a new polymer chain, unless, as in the studied reaction, a proton trap is added).…”
Section: Resultsmentioning
confidence: 90%
“…Limiting in some way the set of equations of the general reaction scheme can be justified by the lack of cyclic oligomers in copolymerization products under certain copolymerization conditions studied. However, we think that neglecting the formation of non‐strained tertiary oxonium cations with three polymeric branches, being the product of the reaction of active species of copolymerization with polymer repeating units4 (shown on the left‐hand side of Scheme ), is not justified and led the authors to disputable conclusions as will be demonstrated below.…”
Section: Resultsmentioning
confidence: 99%
“…Several other crosslinked and linear polyoxetanes are used as amphiphilic polymers, drug delivery systems, organic semiconductors, organic light emitting diodes, organic field‐effect transistors, crosslinkable conjugated polymers, polymeric solar cells, and polymer electrolytes . In addition, trialkyl aluminum/H 2 O catalytic system gives polyoxetanes with well‐controlled molecular weights . Oxetane monomers also undergo cationic ring‐opening copolymerization with six‐ or seven‐membered heterocyclic compounds such as tetrahydropyran, ε ‐caprolactone, 1,3,2‐dioxathiepane‐2‐oxide, spiroorthoester, and spiroorthocarbonate .…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47] In addition, trialkyl aluminum/H 2 O catalytic system gives polyoxetanes with well-controlled molecular weights. 48,49 Oxetane monomers also undergo cationic ring-opening copolymerization with six-or seven-membered heterocyclic compounds such as tetrahydropyran, 50 ε-caprolactone, 51 1,3,2-dioxathiepane-2-oxide, 52 spiroorthoester, 53,54 and spiroorthocarbonate. 55 Additional supporting information may be found in the online version of this article.…”
mentioning
confidence: 99%